2021
DOI: 10.1371/journal.pgph.0000022
|View full text |Cite
|
Sign up to set email alerts
|

Job satisfaction among healthcare workers in Ghana and Kenya during the COVID-19 pandemic: Role of perceived preparedness, stress, and burnout

Abstract: The COVID-19 pandemic has affected job satisfaction among healthcare workers; yet this has not been empirically examined in sub-Saharan Africa (SSA). We addressed this gap by examining job satisfaction and associated factors among healthcare workers in Ghana and Kenya during the COVID-19 pandemic. We conducted a cross-sectional study with healthcare workers (N = 1012). The two phased data collection included: (1) survey data collected in Ghana from April 17 to May 31, 2020, and (2) survey data collected in Gha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
36
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(48 citation statements)
references
References 53 publications
(73 reference statements)
8
36
4
Order By: Relevance
“…This study showed that physician engagement was affected during the COVID-19 pandemic. In contrast to many studies that showed deteriorated results due to having experienced fear, panic, anxiety, depression, and burnout among healthcare workers [ 13 , 16 , 32 , 33 , 34 ], the physician engagement in our survey showed a higher score during the COVID-19 pandemic (4.12 versus 4.06, p -value < 0.001). Hospital management is the key to the success of physician engagement, which has been mentioned in some studies [ 35 , 36 ].…”
Section: Discussioncontrasting
confidence: 99%
“…This study showed that physician engagement was affected during the COVID-19 pandemic. In contrast to many studies that showed deteriorated results due to having experienced fear, panic, anxiety, depression, and burnout among healthcare workers [ 13 , 16 , 32 , 33 , 34 ], the physician engagement in our survey showed a higher score during the COVID-19 pandemic (4.12 versus 4.06, p -value < 0.001). Hospital management is the key to the success of physician engagement, which has been mentioned in some studies [ 35 , 36 ].…”
Section: Discussioncontrasting
confidence: 99%
“…Nonetheless, the short duration of these challenges should not undermine their impact on care provision and on the well-being of maternity SHP. Several studies have documented an increase in stress levels, anxiety and depression among frontline workers during the COVID-19 pandemic, and a systematic review shows that PPE shortage, inconsistent information and long working hours are associated with SHP’s experiences during pandemics and epidemics globally 28 29. Maternity SHP must be included in the priority setting when responding to health system shocks as they constitute a pillar of the WHO’s quality of care model 43 44.…”
Section: Discussionmentioning
confidence: 99%
“…28 A recent study in Ghana and Kenya shows significant declines in job satisfaction and increase in stress and burnout among frontline healthcare workers during the COVID-19 pandemic. 29 In Nigeria, maternal and newborn healthcare providers worried about stigmatisation or discrimination as a result of their potential exposure to COVID-19, and 87% experienced work-related burnout because of the COVID-19 pandemic. 26 In sub-Saharan Africa, large tertiary referral hospitals are designed to primarily provide care for women with high-risk pregnancies, however they also serve large numbers of low-risk women who prefer to seek care in high-level facilities.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study suggests that Ghanaian health workers felt more satisfied and appreciated compared with their Kenyan counterparts. 24 Although the level of satisfaction of the Ghanaian health workers has not been empirically linked to the incentives given to fight the COVID-19 pandemic, it could be one of the hypotheses for further research. Also, while the impact of the incentives granted the Ghanaian health workers on the overall success or otherwise of the pandemic response in the country is yet to be ascertained, an important takeaway for the global health community is that incentives can play an essential part in mobilising the HWF for emergency response.…”
Section: Lessons For Hwf Planning In Future Health Emergenciesmentioning
confidence: 99%